Penegakan dan Perlindungan Hukum Terhadap Satwa Kuskus (Phalanger SPP) yang Dilindungi di Kota Ambon - Fikry Latukau (SASI, 2019)
One of the animals favored by people and can be used as food for some people in Ambon City is cuscus (phalanger spp) is one of the long-tailed marsupial mammals and is also a part of natural resources that is priceless so that its sustainability needs to be maintained through various safeguards. In detail, the regulations concerning these animals are regulated in the regulation of the Minister of Environment and Forestry No. 20 of 2018 concerning the types of plants and animals that are protected. Protected animals are animals that have rarely existed and are therefore protected by various regulations. One of the actions which until now still often occurs and violates the rules in protecting animals is used as food (killed) for some people in Ambon City are cuscus (phalanger spp). The killing of wild animals is an act that has violated the provisions contained in Law No. 5 of 1990 concerning Conservation of Biological Resources and their Ecosystems. Where in article 21 paragraph (2) (a) it has been stated that the prohibition to kill protected animals. In an effort to protect the animals from killing, law enforcement against the trade of protected animals is a process of embodiment of the rules regarding the protection of animals in practice legally in order to realize the goal of protecting protected animals. Research based on normative law research (normative law research) uses normative case studies in the form of legal behavior products, for example reviewing laws. The subject of the study is a law conceptualized as a norm or rule that applies to society and becomes a reference for everyone's behavior. The application of criminal sanctions against some residents of Ambon City who consume cuscus animals (phalanger spp) does not work properly